Nilai-Nilai Pendidikan dalam Novel Kubah di Atas Pasir Karya Zhaenal Fanani: Tinjauan Antropologi Sastra Sebagai Upaya Penyediaan Bahan Ajar Apresiasi Sastra di SMA - Pratiwi, Erlinda Ajeng; , Dra. Main Sufanti, M.Hum (2016)
Purposes of the research are to: describe elements that is structuring novel Kubah di Atas Pasir; describe educational values found in the novel; and make design of teaching materials from results of the research. The research is descriptive-qualitative one. Objects of the research are structure and educational values contained in the novel Kubah di Atas Pasir by Zhaenal Fanani. Data of the research is sentences and words of the novel containing information of teaching materials. Sources of data consisted of novel Kubah di Atas Pasir by Zhaenal Fanani and teachers. Data was collected by using literature, observation, recording and interview techniques. The data was analyzed by using heuristic and hermeneutic reading as well as interactive analysis. Results of the research found that: the theme, namely regardless the outcome, if we want to do something, it should be preceded by praying and efforts. Main character of the novel is Fatikha. She was a pious girl with good attitude. Settings of the story were Ngurawan village, Ar-Rahmah Foundation, Blumbang Precinct, Hiram School and grave. The novel used back and forth storyline. Educational values found in the novel included: (1) hedonism values, readers were presented with stories of Fatikha's struggles such as she should sent her child to school and the story can be a motivator; (2) artistic values, author in conveying story with easy-understood language; (3) cultural values, people were still conducting offerings in graveyard at Maulud month; (4) ethics-moral-religious values, Fatikha was always patient in facing problems and she was always praying to Allah; (5) practical values, the message that can be taken was we should always make efforts and pray. Based on the analysis, 4 materials of teaching can be made, namely: (1) reading a novel; (2) reading a synopsis; (3) analysis of structure; and (4) analysis of educational values: Teachers' responds on the teaching materials indicated that all the teaching materials were relevant with curriculum of 2013 and they were suitable for application in high school. Novel as a teaching material was intended to improve students' appreciation on literature works. Key words: educational values, teaching materials